Indocyanine Green Angiography: A Helpful Tool for Intraoperative Assessment of Upper Extremity Perfusion. Issue 3 (September 2017) - Ghareeb, Paul A.; Neustein, Thomas M.; Fang, Robert C.; Payne, Diane E.
Abstract : Assessment of tissue perfusion can be a challenge for the hand surgeon. Indocyanine green (ICG) angiography has been shown to be a valuable adjunct to physical examination and clinical judgment when there is a concern for tissue perfusion. The use of this technology has risen sharply in recent years in reconstructive surgery. Applications of ICG angiography have been developed throughout the field of surgery, including breast surgery, free tissue transfer, bowel surgery, neurosurgery, and lymphatic reconstruction. In this study, we discuss the novel applications of ICG angiography within the field of upper extremity surgery, and provide specific case examples of its successful use.